Influence of different surface treatment protocols on the bond strength of itrite stabilized polycrystalline zirconia Itry stabilized polycrystalline tetragonal (Research, Society and Development, 2020)
Evaluate the influence of different surface treatment protocols on shear bond strength in zirconia ceramics. A hundred zirconia cylinders were made using a CAD/CAM system. The specimens were divided into 10 groups: No treatment; Clearfil Ceramic Primer; Scotch bond Universal; Clearfil Ceramic Primer + Scotch bond Universal; 50% hydrofluoric acid + Scotch bond Universal; Airborne-particle abrasion; Airborne-particle abrasion + Clearfil Ceramic Primer; Airborne-particle abrasion + Scotch bond Universal; Airborne-particle abrasion + Clearfil Ceramic Primer + Scotch bond Universal; Airborne-particle abrasion+50% hydrofluoric acid + Scotch bond Universal. All specimens were cemented with Panavia F 2.0, stored in distilled water, and then thermo cycled. The shear bond strength test was performed in a universal testing machine. Fractographic and surface zirconia analysis was done with a stereomicroscope, SEM and WDS. Data were analyzed using Pearson’s chi-square test, Fisher exact test, and the Kruskal-Wallis test. The highest shear bond strength values were observed in the groups treated with hydrofluoric acid, besides, these groups did not show pre-test failure. The predominant failure mode was adhesive. Among the surface treatment protocols evaluated, 50% hydrofluoric acid conditioning associated with the Scotchbond Universal adhesive system offers higher values of shear bond strength to the zirconia, regardless of the use of microblasting.